Magnetic and resonance properties of the two-dimensional S = 1 compound Ni5(TeO3)4Cl2 with frustrated geometry - Gnatchenko, S.L.; Kobets, M.I.; Khatsko, E.N.; Baran, M.; Szymczak, R.; Lemmens, P.; Berger, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2008)
The magnetic and magnetoresonance properties of a new single-crystal compound Ni5(TeO3)4Cl2 arestudied. The measurements of the magnetization and magnetic susceptibility of the crystal in a wide temperature range (5–300 K) made it possible to conclude that Ni5(TeO3)4Cl2 is a quasi-two-dimensional antiferromagnet with the easy magnetization axis a* directed perpendicular crystallographic plane bc and a magnetic ordering temperature TN ≈ 21 K. The resonance measurements at 4.2 K in wide range of frequencies (25–105 GHz) and magnetic field (up to 200 kOe) permitted us to obtain the frequency–field dependence of AFMR spectrum for a field applied along the easy magnetization axis a*. It is shown that the magnetic field directed along the antiferromagnetism axis (H||a*) induces the magnetic phase transition of a spin-flop type which is found to be Hsf ≈120 kOe. The magnetic resonance experimental data are described qualitatively in model of the biaxial antiferromagnet.